(x^-3 x^-3)^2

Rebekah Shelton

Rebekah Shelton

Answered question

2022-02-10

(x^-3 x^-3)^2

Answer & Explanation

April Acosta

April Acosta

Beginner2022-02-11Added 11 answers

Use (a^n)^m=a^(n*m)
(x^-3x^-3)^2=x^(-3*2)x^(-3*2)
(x^-3x^-3)^2=x^-6x^-6
Use a^n+a^m=a^(a+m)
(x^-3x^-3)^2=x^-12
Use a^-n=1/a^n
(x^-3x^-3)^2=1/x^12 - Answer
hotlegsaprile2u

hotlegsaprile2u

Beginner2022-02-12Added 21 answers

Answer with explanation

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get an expert answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?